L’abitare dei rifugiati in Calabria. Pratiche e politiche, oltre l’emergenza - D’Agostino, Mariafrancesca (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Within a framework where forced migration flows continue to grow, we will examine the models of inclusion housing provided to refugees and asylum seekers in Calabria. We will discuss the political, social and cultural impacts of these divergent models to show how, beyond the temporal limits and bureaucracy which characterize the institutional system of reception, informal housing is turning into a fundamental means for social transformation, giving legitimacy to new post-national identities and practices of citizenship.